Physiological Fontan Procedure - Corno, Antonio F.; Owen, Matt J.; Cangiani, Andrea; Hall, Edward J. C.; Rona, Aldo (Frontiers in Pediatrics, 2019)
Objective: The conventional Fontan circulation deviates the superior vena cava (SVC=1/3 of the systemic venous return) towards the right lung (3/5 of total lung volume) and the inferior vena cava (IVC=2/3 of the systemic venous return) towards the left lung (2/5 of total lung volume). A “physiological” Fontan deviating the SVC towards the left lung and the IVC towards the right lung was compared with the conventional setting by computational fluid dynamics, studying if this setting achieves a more favorable hemodynamic than the conventional Fontan circulation. Materials and Methods: An in-silico 3D parametric model of the Fontan procedure was developed using idealized vascular geometries with invariant sizes of SVC, IVC, right pulmonary artery (RPA), and left pulmonary artery (LPA), steady inflow velocities at IVC and SVC, and constant equal outflow pressures at RPA and LPA. These parameters were set to perform finite-volume incompressible steady flow simulations, assuming a single-phase, Newtonian, isothermal, laminar blood flow. Numerically converged finite-volume mass and momentum flow balances determined the inlet pressures and the outflow rates. Closed-path numerical integration of energy fluxes across domain boundaries determined the flow energy loss through the Fontan circulation. The comparison evaluated: 1) mean IVC pressure; 2) energy loss rate; 3) kinetic energy maximum value throughout the domain volume. Results: The comparison of the physiological versus conventional Fontan provided these results: 1) mean IVC pressure 13.9mmHg versus 14.1mmHg (= 0.2mmHg reduction); 2) energy loss rate 5.55mW versus 6.61mW (= 16% reduction); 3) kinetic energy 283J/m3 versus 396J/m3 (= 29% reduction). Conclusions: A more physiological flow distribution is accompanied by a reduction of mean IVC pressure and by substantial reductions of energy loss rate, and peak kinetic energy. The potential clinical impact of these hemodynamic changes in reducing the incidence and severity of the adverse long-term effects of the Fontan circulation, in particular liver failure and protein-losing enteropathy, still remains to be assessed and will be the subject of future work.